Organizational Commitment Ditinjau dari Psychological Ownership pada Karyawan PT Capella Dinamik Nusantara Medan - Jovian Julius Julius; Diny Atrizka; Rianda Elvinawanty (Psyche 165 Journal, 2020)
The purpose of this study is to find out about the relationship between organizational commitment and psychological ownership. The hypothesis that the researchers propose in this study is that there is a positive and significant relationship between organizational commitment and psychological ownership, assuming that the higher the organizational commitment, the higher the psychological ownership and conversely. The selection of participants for this study used a sampling method, namely purposive sampling. The sample of this research is 141 employees who are permanent employees who have more than 1 year of service at PT. Capella Dinamik Nusantara Medan. Data collected by researchers, comes from the collection results with a scale that has been prepared with reference to the theoretical dimensions used by researchers to measure organizational commitment and psychological ownership. The correlation coefficient obtained was 0.613 (p <0.05). These results indicate that there is a positive and significant relationship between organizational commitment and psychological ownership. The results of this study contribute to the Industrial & Organizational Psychology sector in particular to increase employee commitment.